Nonlinear association between platelet to albumin ratio and disease activity in patients with early rheumatoid arthritis - Lina Leng; Jingfang Shen; Lianju Li; Junfeng Li; Xiaoli Li; Dengxiang Liu (Scientific Reports)
Abstract The relationship between the platelet to albumin ratio (PAR) and the disease activity of early rheumatoid arthritis (ERA) remains to be elucidated. This cross-sectional study included 372 patients with ERA who were hospitalized at Xingtai People’s Hospital between January 2022 and January 2024. Multiple linear regression analysis was employed to assess the correlation of PAR with Disease Activity Score 28 (DAS28) using erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP), and then generalized additive models were used to explore their relationship. After accounting for confounding variables, a positive correlation was observed between the PAR and DAS28-ESR and DAS28-CRP in ERA patients (β (95% CI): 0.20 (0.08, 0.32) and 0.20 (0.08, 0.33), respectively), and the general trends were consistent from the lowest tertile group (T1) to the highest tertile group (T3). Furthermore, a nonlinear relationship was identified between PAR and both DAS28-ESR and DAS28-CRP. Threshold effect analysis indicated that a value of 13.73 was a significant inflection point. In brief, PAR has a threshold effect on the disease activity of ERA. Increased PAR levels were independently positive associated with DAS28-ESR and DAS28-CRP among ERA patients with PAR < 13.73.